Adaptive LMBP training‐based icosϕ control technique for DSTATCOM. Issue 3 (19th December 2019) - Mangaraj, Mrutyunjaya; Panda, Anup Kumar; Penthia, Trilochan; Dash, Asish Ranjan
Abstract : In this study, the design and implementation of a new hybrid soft computing control technique called Levenberg–Marquardt backpropagation (LMBP)‐based icosϕ is proposed. Two different compensation techniques are evaluated for the performance analysis of three‐phase three‐wire (3P3W) voltage source converter (VSC)‐based DSTATCOM. The first one is the conventional icosϕ control technique whereas the other one is called the LMBP‐based icosϕ control technique. The better power quality of the system is obtained using the proposed control algorithm by maintaining a less voltage across the capacitor as compared to the conventional one. So, the reduction in the size of the DSTATCOM is realised by the LMBP‐based control algorithm. Furthermore, the performance parameters such as load balancing, harmonics elimination, power factor improvement, and voltage regulation are evaluated under both balanced and unbalanced loading conditions as per the IEEE guidelines. The effectiveness of the proposed controller is studied in the MATLAB/Simulink environment and also validated with a low power rated prototype experimental results.